Perioperative Cardiometabolic Targets and Coronary Artery Bypass Surgery Mortality in Patients With Diabetes - John P. Skendelas; Donna K. Phan; Patricia Friedmann; Carlos J. Rodriguez; Daniel Stein; Armin Arbab‐Zadeh; Stephen J. Forest; Leandro Slipczuk (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Coronary artery bypass graft (CABG) surgery represents the preferred revascularization strategy for most patients with diabetes and multivessel disease. We aimed to evaluate the role of optimized, perioperative cardiometabolic targets on long‐term survival in patients who underwent CABG. Methods and Results Single‐institution retrospective study was conducted in patients with diabetes who underwent CABG between January 2010 and June 2018. Demographic, surgical, and cardiometabolic determinants were identified during the perioperative period. Clinical characteristics and longitudinal survival outcomes data were obtained. A total of 1534 patients with CABG were considered for analysis and 1273 met inclusion criteria. The mean age of patients was 63.3 years (95% CI, 62.7–63.8 years), and most were men (65%) and Hispanic or Latino (47%). Comorbidities included hypertension (95%) and dyslipidemia (88%). In total, 490 patients (52%) had a low‐density lipoprotein cholesterol level >70 mg/dL. Furthermore, 390 patients (31%) had uncontrolled systolic blood pressure >130 mm Hg. Last, only 386 patients (29%) had a hemoglobin A1c level between 6% and 7%. At 5 years, 121 patients (10%) died. Failure to achieve goal systolic blood pressure was associated with all‐cause (hazard ratio [HR], 1.573; 95% CI, 1.048–2.362 [P=0.029]) and cardiovascular (HR, 2.023; 95% CI, 1.196–3.422 [P=0.009]) mortality at 5 years post‐CABG. In contrast, prescription of a statin during the perioperative interval demonstrated a protective effect for all‐cause (HR, 0.484; 95% CI, 0.286–0.819 [P=0.007]) and cardiovascular (HR, 0.459; 95% CI, 0.229–0.920 [P=0.028]) mortality. There was no association between achievement of low‐density lipoprotein cholesterol, triglycerides, non–high‐density lipoprotein cholesterol, or hemoglobin A1c level goals and mortality risk at 5 years. Conclusions Among patients with diabetes, blood pressure control and statin therapy were the most important perioperative cardiometabolic survival determinants 5 years after CABG.